Modular Functional-Metabolic Coupling Alterations of Frontoparietal Network in Schizophrenia Patients - Xiang, Qiong; Xu, Jiale; Wang, Yingchan; Chen, Tianyi; Wang, Jinhong; Zhuo, Kaiming; Guo, Xiaoyun; Zeljic, Kristina; Li, Wenli; Sun, Yu; Wang, Zheng; Li, Yao; et al. (Frontiers in Neuroscience, 2019)
Background: Brain functional dysconnectivity as well as altered network organization have been demonstrated in schizophrenia. Brain networks are increasingly understood to exhibit modular community structure, which provides advantages in robustness and functional adaptivity. The frontoparietal network (FPN) serves as an important functional module, and metabolic and functional alterations in the FPN are associated with the pathophysiology of schizophrenia. However, how intra-modular biochemical disruptions lead to inter-modular dysfunction of FPN remains unclear. In this study, we aim to investigate alterations in modular functional-metabolic coupling of FPN in schizophrenia patients. Methods: We combined resting-state functional magnetic resonance imaging (rs-fMRI) and magnetic resonance spectroscopy (MRS) technology and acquired multimodal neuroimaging data in 20 schizophrenia patients and 26 healthy controls. For MRS, the dorsolateral prefrontal cortex (DLPFC) region within FPN was explored. Metabolites including gamma aminobutyric acid (GABA), N-aspart-acetyl (NAA) and glutamate + glutamine (Glx) were quantified, using LCModel software. A graph theoretical approach was applied for functional modular parcellation. The relationship between inter/intra-modular connectivity and metabolic concentration was examined using Pearson correlation analysis. Moreover, correlations with schizophrenia symptomatology were investigated by Spearman correlation analysis. Results: The functional topological network consisted of six modules in both subject groups, namely, the default mode, frontoparietal, central, hippocampus, occipital, and subcortical modules. Inter-modular connectivity between frontoparietal and central modules, and frontoparietal and hippocampus modules was decreased in the patient group compared to healthy controls, while the connectivity within frontoparietal modular increased in patient group. Moreover, a positive correlation between frontoparietal and central module functional connectivity and NAA in DLPFC was found in healthy control group (r=0.614, p=0.001), but not in the patient group. Significant functional dysconnectivity between frontoparietal and limbic modules was correlated with clinical symptom of patients. Conclusions: The present study examined the links between functional connectivity and neuronal metabolic level in the DLPFC of SCZ. Impaired functional connectivity of frontoparietal areas in SCZ may be partially explained by a neurochemical-functional connectivity decoupling effect. This disconnection pattern can further provide useful insights in the cognitive and perceptual impairments of schizophrenia in future studies.